Quantitative spinal cord MRI in radiologically isolated syndrome. Issue 2 (March 2018) - Alcaide-Leon, Paula; Cybulsky, Kateryna; Sankar, Stephanie; Casserly, Courtney; Leung, General; Hohol, Marika; Selchen, Daniel; Montalban, Xavier; Bharatha, Aditya; Oh, Jiwon
Abstract : Objectives: To assess whether quantitative spinal cord MRI (SC-MRI) measures, including atrophy, and diffusion tensor imaging (DTI) and magnetization transfer imaging metrics were different in radiologically isolated syndrome (RIS) vs healthy controls (HCs). Methods: Twenty-four participants with RIS and 14 HCs underwent cervical SC-MRI on a 3T magnet. Manually segmented regions of interest circumscribing the spinal cord cross-sectional area (SC-CSA) between C3 and C4 were used to extract SC-CSA, fractional anisotropy, mean, perpendicular, and parallel diffusivity (MD, λ⊥, and λ|| ) and magnetization transfer ratio (MTR). Spinal cord (SC) lesions, SC gray matter (GM), and SC white matter (WM) areas were also manually segmented. Multivariable linear regression was performed to evaluate differences in SC-MRI measures in RIS vs HCs, while controlling for age and sex. Results: In this cross-sectional study of participants with RIS, 71% had lesions in the cervical SC. Of quantitative SC-MRI metrics, spinal cord MTR showed a trend toward being lower in RIS vs HCs ( p = 0.06), and there was already evidence of brain atrophy ( p = 0.05). There were no significant differences in SC-DTI metrics, GM, WM, or CSA between RIS and HCs. Conclusion: The SC demonstrates minimal microstructural changes suggestive of demyelination and inflammation in RIS. These findings are in contrast to established MS and raise the possibility that the SC may play an important role in triggering clinical symptomatology in MS. Prospective follow-up of this cohort will provide additional insights into the role the SC plays in the complex sequence of events related to MS disease initiation and progression.